Codependent no more How to Stop Controlling Others and Start Caring for Yourself - Beattie, Melody (New York, NY Hazeldon, 1987)
Melody Beattie's compassionate and insightful look into codependency--the concept of losing oneself in the name of helping another--has guided millions of readers toward the understanding that they are powerless to change anyone but themselves and that caring for the self is where healing begins. Is someone else's problem your problem? If, like so many others, you've lost sight of your own life in the drama of tending to a loved one's self-destructive behavior, you may be codependent--and you may find yourself in this book. With personal reflections, exercises, and instructive stories drawn from Beattie's own life and the lives of those she's counseled, Codependent No More helps you break old patterns and maintain healthy boundaries and offers a clear and achievable path to healing, hope, freedom, and happiness. This revised edition includes an all-new chapter on trauma and anxiety--subjects Beattie has long felt necessary to address within the context of codependency--making it even more relevant today than it was when it first entered the national conversation over 35 years ago." Provided by the publisher
D., 4/02
Keywords: Substance abuse--Patients--Family; Self-care, Health